Theoretical Investigations into Potential Optically Transparent Insulating Materials for Efficient Solar Thermal Energy Conversion - Singh, Kirtanprakash (My University, 2024)
As concentrating solar collectors are very expensive and also concentrating solar collectors have low optical efficiency at higher concentration ratios so due to this reason an alternative method of solar collection which is economical and also can be used to attain higher temperatures of the receiver or absorber plate is required. Therefore, to achieve this optically transparent insulating materials are used. By using optically transparent insulating materials intermediately high temperatures could be achieved at low optical solar concentration ratio. If we use an aerogel as an optically transparent insulating material then the maximum percentage increase of 5.5 percent was observed in case of pure scattering medium with respect to the case of pure absorbing medium but this maximum percentage increase of 5.5 percent in the absorber or receiver temperature was found when the optical depth in the solar region is 1 and the thickness of an aerogel medium is 30 mm. So, by varying the conditions of the medium, by varying the thermophysical properties of the medium and also by varying the physical properties like thickness of the medium absorber or receiver plate temperature variation was found out and analyzed.
Keywords: Optically transparent insulating materials (OTIMs); Aerogel; Solar thermal; Thermal losses; Stagnation temperature